Concept and Legal Status of Underhand Marriages According to Indonesian National Law - Jamil, Jamil (Jurnal Idea Hukum, 2024)
Marriage is a means for humans to improve the quality and quantity of their lives. Thus, humans are very dependent on the institution of marriage, including the Indonesian people. Therefore, it is appropriate for the Indonesian people to protect it by placing its regulation in the 1945 Constitution. As a result, in addition to every citizen being guaranteed the right by the state to form a family through marriage, the state is also responsible for protecting the institution of marriage. However, this does not mean marriage can be conducted without discrimination due to various factors. As a result, it has encouraged many Indonesians to perform marriages outside the procedure such as underhand marriages. There are two problems in this study: 1) What is the concept of underhand marriage according to Indonesian national law? 2) What is the legal status of underhand marriage according to Indonesian national law? To discuss the two problems, a normative type of legal research is used, with secondary data sourced from library materials in the field of marriage law, while to obtain data the document study method is used, and data processing with the method of systematization. As for the approach, a statutory approach is used. The results and findings of this study are: that underhand marriages that have fulfilled certain pillars and conditions that have been determined in their respective religious laws are valid (legal) according to Indonesian national law. From these findings, the author concludes that;  1) An underhand marriage is a marriage between a man and a woman, which fulfills the pillars and conditions stipulated in their respective religious laws and laws and regulations, but is not recorded at the government agency authorized to do so; 2) The legal status of underhand marriage, seen from Indonesian national law, is a legal institution (legal) according to Indonesian national law. Suggestions that can be given by the author are: that if 1) It is important to socialize the concept of underhand marriage to the community so that they understand the pillars and conditions, so that they do not consider it equivalent to an unofficial relationship (kumpul kebo), 2) It is necessary to improve marriage regulations, especially Law No. 1 of 1974. The government's 2019 efforts that only focus on the marriage age limit are inadequate; the practice of underhand marriage also needs attention. If revision is difficult, the government must educate the public about Supreme Court Jurisprudence No. 57 K/Pdt/2005, which states that couples without a marriage certificate are still considered husband and wife if they are registered on one family card.